Relationships between exposure to urban green spaces, physical activity and self-rated health. (July 2015) - Pietilä, Miisa; Neuvonen, Marjo; Borodulin, Katja; Korpela, Kalevi; Sievänen, Tuija; Tyrväinen, Liisa
Abstract: The environment surrounding residences and its recreational and commuting opportunities are believed to affect human health and well-being. To provide scientific evidence for the mechanisms of influence of the types of environments on human well-being, this study examined how the presence of and access to green spaces is related to the level of physical activity and self-rated health. The study focused on the mediating role of outdoor physical activity, utilizing a dataset from a comprehensive, cross-sectional nationwide survey, which included the number of outdoor recreation visits to close-to-home green spaces and respondents' self-rated health status. The survey data were supplemented with precise, GIS-derived data of each respondent's exposure to green spaces, and the relationships were tested using path analyses. The study demonstrated that the presence of and access to green space is evident in the suburbs, where outdoor recreation was related to leisure time physical activity and to self-rated health. Thus, in order to promote health to suburban residents, access to close-to-home green spaces suitable for recreation should be secured. In contrast, in more urban residential areas, green spaces were more connected to frequent physical activity in association with commuting, indicating that investing in infrastructure for safe walking and bicycling could promote public health. Management implications: The research results contribute to strengthening the role and importance of close-to-home recreational opportunities in urban green spaces. Easy accessibility to green spaces should be an important objective in the management and planning of urban and suburban forests and other green spaces. Close-to-home recreation opportunities are particularly vital for older people. If green spaces are also developed for commuting, health and well-being benefits could be realized via increased overall physical activity.